Bowel frequency (night) and urgent defecation are improved by budesonide foam in patients with ulcerative colitis: a retrospective observational study - Ryosuke Miyazaki; Toshiyuki Sakurai; Mariko Shimada; Yuko Iwashita; Naoki Shibuya; Yoshihiro Akita; Haruna Miyashita; Yuki Maruyama; Masayuki Saruta (BMC Gastroenterology, 2022)
Abstract Introduction Patients with ulcerative colitis (UC) are known to have a significantly poor quality of life due to bowel frequency (night) and urgent defecation. Budesonide foam is a topical medication that was approved in Japan in 2017 for the treatment of UC. However, its efficacy in the treatment of bowel frequency (night) or urgent defecation is unknown. This study aimed to explore the efficacy of budesonide foam for the alleviation of these symptoms. Methods UC patients who received budesonide foam between December 2017 and January 2020 at the Jikei University School of Medicine in Tokyo were enrolled. The simple clinical colitis activity index (SCCAI) was evaluated at the start of budesonide foam treatment and 2 and 6 weeks later in patients who initially scored ≥ 1 for bowel frequency (night) and urgent defecation, respectively. We also studied the effect of budesonide foam on remaining symptoms in patients who had used 5-aminosalicylic acid (5-ASA) topical treatment, those with SCCAI ≥ 3, and those in remission with residual symptoms (SCCAI 1 or 2). Results Of the 233 enrolled patients, 102 were eligible for the study. In 36 patients with bowel frequency (night) treated with budesonide foam were significantly effective, score in SCCAI decreased from 1.17 ± 0.45 at baseline to 0.53 ± 0.61 at week 2 (p < 0.0001) and 0.17 ± 0.38 at week 6 (p < 0.0001). In 45 patients with urgent defecation score in SCCAI decreased significantly from 1.33 ± 0.52 at baseline to 0.44 ± 0.59 at week 2 (p < 0.0001) and 0.22 ± 0.40 at week 6 (p < 0.0001). Of 22 patients who switched from topical 5-ASA administration to budesonide foam, nine at week 2 (41%) and 11 (50%) at week 6 were improved with no symptoms, and there were no cases of worsened symptoms. No severe side effects associated with budesonide foam were observed. Conclusion Budesonide foam administration significantly improves both bowel frequency (night) and urgent defecation-related UC activity and is also effective for the patients who were refractory to topical 5-ASA administration.